An Overview of Students’ HOTS to Develop Instructional Kit for Disaster Mitigation based on Vocational Education - Novyanti, Yuwita; Rahmayanti, Henita; Azwar, Sylvira Ananda; Ichsan, Ilmi Zajuli; Singh, Charanjit Kaur Swaran; Rahman, Md. Mehadi; Darussyamsu, Rahmawati; Ali, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2021)
Flooding that occurred recently has become a very detrimental disaster for the victims. This flood disaster is still a concern for people in Indonesia. Flood mitigation needs to be done to all levels of society, especially vocational school students. Vocational school students must be responsive in any situation because, after graduation, they are ready to work. Disaster mitigation is essential to be included in learning at school. Disaster mitigation is also related to the Higher-Order Thinking Skills (HOTS) to always be ready and alert. In measuring vocational school students' understanding of disaster mitigation, initial research was carried out related to disaster mitigation and HOTS. The research subjects were 100 students of Vocational School in Jakarta who were randomly selected. This study used Google Forms as a data collection technique. The results showed that the students’ HOTS score was still low. The results showed that the Students’ HOTS scores on flooding were still low. The average score obtained by the whole students was 43.34. The male students obtained 30.27, and the female students obtained 45.97. All schools in Indonesia should implement early mitigation education that is integrated with HOTS learning.